2015
DOI: 10.1103/physrevb.91.125431
|View full text |Cite
|
Sign up to set email alerts
|

Ultrafast phonon dynamics of epitaxial atomic layers of Bi on Si(111)

Abstract: Ultrathin bismuth (Bi) layers on Si(111)-7 × 7 undergo a structural phase transformation with reducing the number of atomic layers at 3 bilayers (BL). We investigate the phonon dynamics of the Bi films close to the phase transformation by pump-probe reflectivity measurements. Coherent A 1g and E g phonons at 3 and 2 THz are clearly observed for the Bi layers with thicknesses down to 3 BL, confirming their rhombohedral crystalline structure. The A 1g frequency exhibits an abrupt redshift and splits into two com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…We note that the frequencies of optical and acoustical modes are softened upon the inclusion of spin-orbit coupling in interatomic forces. Experiments [42] on a Bi(111) slab on the Si(111) surface measured frequencies of E g and A 1g modes as = 74 cm −1 and = 102 cm −1 , respectively, which are close to the values of = 62 cm −1 and = 102 cm −1 calculated in this paper. These calculated frequencies also agree with earlier calculations [43,44] predicting the frequency of E g in the range of 66 cm −1 < < 69 cm −1 and of A 1g in the range of 99 cm −1 < < 103 cm −1 .…”
Section: D Bismuth Crystalsupporting
confidence: 88%
“…We note that the frequencies of optical and acoustical modes are softened upon the inclusion of spin-orbit coupling in interatomic forces. Experiments [42] on a Bi(111) slab on the Si(111) surface measured frequencies of E g and A 1g modes as = 74 cm −1 and = 102 cm −1 , respectively, which are close to the values of = 62 cm −1 and = 102 cm −1 calculated in this paper. These calculated frequencies also agree with earlier calculations [43,44] predicting the frequency of E g in the range of 66 cm −1 < < 69 cm −1 and of A 1g in the range of 99 cm −1 < < 103 cm −1 .…”
Section: D Bismuth Crystalsupporting
confidence: 88%
“…362 Their experimental results and first principles calculations showed that the topological nature of Bi (110) films is sensitive to the atomic buckling which is tunable via charge doping and could be controlled by choosing different substrates on which Bi(110) films are grown. 362 While most Bi ultrathin films were grown on the Si(111) substrate, [363][364][365][366] recently, Reis et al 367 synthesized a Bi honeycomb structure with a relatively large gap of 0.8 eV on top of SiC(0001). Few-layers bismuthene, which was synthesized very recently by the sonochemical exfoliation method had an optical pulse value of 652 femtoseconds and is now considered as an excellent material for ultrafast absorber devices.…”
Section: Resultsmentioning
confidence: 99%
“…17 Besides, a large gap of ∼0.8 eV was experimentally detected in monolayer bismuthene on SiC (0001) at RT, making it a candidate for a high-temperature quantum spin Hall material. 18,19 In addition, owing to the small electron effective mass (<0.03m 0 ) 20 and extremely long mean free path, 21 Bi displays a large magnetoresistance effect. Meanwhile, single-crystal bulk bismuth has a high mobility (∼10 6 cm 2 V −1 s −1 ), 22 suggesting its potential application in field effect transistors, but a low carrier density (∼10 17 cm −3 ) 23 due to a small band overlap that can be tuned by the thickness.…”
Section: Introductionmentioning
confidence: 99%